2020
DOI: 10.4236/ojvm.2020.101001
|View full text |Cite
|
Sign up to set email alerts
|

Group A Rotavirus Genotypes among Calf Herds in Southwest Nigeria and Implications for Human Rotavirus Vaccines’ Efficiency

Abstract: Rotaviruses have been widely reported to be associated with diarrhea in humans but fewer studies abound on other mammalian species. This prospective study was conducted to detect and characterize Rotaviruses from freely ranged migratory herds of cattle in Ekiti and Ondo states, Nigeria with a view to further expanding knowledge on rotaviruses, possible animal-human interspecies transmission and impacts on vaccine efficiency. By convenience sampling, between September 2014 and February 2015, stool samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
2
Order By: Relevance
“…The present study showed that 7 (8.54%) of 82 diarrheic fecal samples of investigated calves were positive by ICA. Our result of ICA was lower than those of other studies [1,12,13] in which rate of Rotavirus infection in serologically positive enteric calves by ICA was 15.63%, 12.50% and 10%, respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…The present study showed that 7 (8.54%) of 82 diarrheic fecal samples of investigated calves were positive by ICA. Our result of ICA was lower than those of other studies [1,12,13] in which rate of Rotavirus infection in serologically positive enteric calves by ICA was 15.63%, 12.50% and 10%, respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…The present study showed that 7 (8.54%) of 82 diarrheic fecal samples of investigated calves were positive by ICA. Our result of ICA was lower than those of other studies [2,14,15] in which rate of Rotavirus infection in serologically positive enteric calves by ICA was 15.63%, 12.50% and 10%, respectively. Such variations in rate of Rotavirus infection in examined calves may be due to geographical variation, hygienic measures, environmental conditions, difference in timing of samples collection, clinical phase of the disease is a suitable time for sampling to obtain the optimum result from a test [11].…”
Section: Discussioncontrasting
confidence: 90%
“…They indicated that percentage of Rotavirus seropositive enteric cases was 35.25%, and 53.6%, respectively. Contrariwise,[10,18,19] indicated that rate of Rotavirus infection in enteric calves was 36%, 15.63% and 12.50%, respectively. Such variations in rate of infection of Rotavirus in enteric calves may be attributed to geographical variation, difference in timing of samples collection, clinical phase of the disease is a suitable time for sampling to obtain the optimum result from a test, hygienic measures and environmental conditions.…”
mentioning
confidence: 99%